Two-dimensional GaP monolayer with tunable electrical and optical properties (Journal of the College of Basic Education, 2023)
The optical characteristics of two-dimensional (2D) monolayer formations in GaP. According to the predicted binding energies, the GaP monolayers are in constant contact. GaP monolayer was revealed to be semiconducting, with gaps of 2.080 eV. Furthermore, the predicted optical properties indicate that the GaP monolayer will absorb light at wavelengths ranging from infrared to ultraviolet. As a result, GaP monolayer should be appealing for visible-light communication and photocatalytic devices. It is possible to determine that this layer is kinematically stable by studying the form of the phonon, as all frequencies have positive values and there are no negative values for frequency. It is also worth noting that the frequency values exceed 1150 cm-1. Finally, the unexpectedly good properties of GaP monolayer are expected to be used in a variety of combinations in solar cells, field-effect transistors, catalysts, and optical devices.